Physical and psychiatric comorbidity among patients with severe mental illness as seen in Uganda - Mpango, Richard Stephen; Ssembajjwe, Wilber; Rukundo, Godfrey Zari; Birungi, Carol; Kalungi, Allan; Gadow, Kenneth D.; Patel, Vikram; Nyirenda, Moffat; Kinyanda, Eugene (MedRxiv, 2020)
This study established the prevalence of physical and psychiatric comorbidity and associated risk factors among 1,201 out-patients with severe mental illness (SMI) attending Butabika and Masaka hospitals in Uganda. Participants completed an assessment battery; structured, standardized and locally translated instruments. SMIs were established using the MINI International Neuropsychiatric Interview version 7.2. We used logistic regression to determine the association between physical and psychiatric comorbidity and risk factors. Prevalence of physical and psychiatric comorbidity was 13.1 %. Childhood sexual abuse (aOR 1.06, 95% CI 1.03 -1.10, P=0.001), sexual abuse in adulthood (aOR 2.22, 95% CI 1.60 - 3.08, P<0.001), childhood physical abuse (aOR 1.07, 95% CI 1.03 - 1.10, P<0.001) and physical abuse in adulthood (aOR 1.69, 95% CI 1.30 - 2.20, P<0.001) were associated with an increased risk of having comorbid psychiatric and physical disorders. Emerging healthcare models in Uganda should optimize care for people with physical and psychiatric comorbidity
Keywords: Physical and psychiatric comorbidity; Out-patients; Uganda; Mental Illness